Instrumentos jurídicos de planejamento da ocupação urbana como garantia de um município ambientalmente sustentável - Vanin, Fábio Scopel (My University, 2014)
The municipality, autonomous entity of the Federation in Brazil is responsible for the exercise of many powers, among which is the implementation of urban policy through the planning of the occupation, with the use of legal instruments that guarantee an Environmentally Sustainable City. The identification of the precepts of the city that is environmentally sustainable, can be searched at the headquarters of urban sustainability along with an approach to the complex context in which it is being inserted into the site, since it is influenced by global guidelines, the disorderly process of urbanization and environmental crisis, characterized by risk. The instruments to be used in their construction, are referred in the City Statute, with the main one is the Master Plan, however, this relationship should not be limited to them, may be added, among others, Building Code, the Code of Postures and Municipal Code of the Environment. In the implementation of these instruments are present some barriers, including the difficult real estate market regulation, the complex process of building cross-disciplinary and epistemic and the dilemmas of democratic management of cities. In addition to the overcoming of these barriers, the instruments should be linked to the guidelines of the City Statute, the Master Plan, should respond to the dynamic socioeconomic and environmental issues, Local Governments, should have a promoter position, articulating their skills and all other entities, and legal instruments, be systematic and based on common principles and objectives. The understanding of these aspects of global, historical and socio-economic is necessary for the creation of effective legal instruments of urban planning of the occupation, which will ensure an environmentally sustainable city. Adopted as the method of dialectical approach, in order that the work enters the world of phenomena by means of their reciprocal action. Moreover, as procedural method was chosen structuralist, that part of the analysis to a concrete phenomenon, then transpose it to the abstract level and vice versa, see the reality of the internal point of view of various phenomena.
O Município, ente autônomo da Federação no Brasil, é responsável pelo exercício de inúmeras competências, dentre as quais está a execução da política urbana através do planejamento da ocupação, com a utilização de instrumentos jurídicos que garantam um Município Ambientalmente Sustentável. A identificação de preceitos do que é Município ambientalmente sustentável pode ser buscado nas matrizes de sustentabilidade urbana, juntamente com uma abordagem do complexo contexto em que está inserido o ente local, uma vez que é influenciado por diretrizes globais, pelo desordenado processo de urbanização e pela crise ambiental, caracterizada pelo risco. Os instrumentos a serem utilizados na sua construção estão previstos no Estatuto da Cidade, tendo como o principal deles o Plano Diretor. Entretanto, esta relação não deve limitar-se a eles, podendo ser adicionados, entre outros, o Código de Obras, o Código de Posturas e o Código Municipal do Meio Ambiente. Na implementação destes instrumentos estão presentes algumas barreiras, entre as quais a difícil regulação do mercado imobiliário, o complexo processo de construção transdisciplinar e epistêmico e os dilemas da gestão democrática das cidades. Além da superação destas barreiras, os instrumentos devem estar vinculados às diretrizes do Estatuto da Cidade; o Plano Diretor, responder ao dinamismo socioeconômico e as questões ambientais; os Governos Locais, ter uma posição promotora, articulando suas competências e com os demais entes; e os instrumentos jurídicos, estarem sistematizados e baseados em princípios e objetivos comuns. O entendimento destes aspectos globais, históricos e socioeconômicos é necessário para a construção de instrumentos jurídicos efetivos de planejamento da ocupação urbana, que garantirão um Município Ambientalmente Sustentável. Adotou-se como método de abordagem o dialético, tendo em vista que o trabalho penetra o mundo dos fenômenos por meio de sua ação recíproca. Além disso, como método procedimental optou-se pelo estruturalista, que parte da análise de um fenômeno concreto para, em seguida, transpô-lo ao nível abstrato e vice-versa, vendo a realidade concreta do ponto de vista interno dos diversos fenômenos.
Keywords: Direito; Municípios; Planejamento urbano; Meio ambiente; Sustentabilidade urbana; Estatuto da cidade; Plano diretor; Direito urbanístico; Direito ambiental; Desenvolvimento sustentável; Municipality; Urban planning; Environment; Urban sustainability; City statute; Master plan; City planning and redevelopment law; Environmental law; Sustainable development